KEARIFAN MASYARAKAT LOKAL SUKU LAUJE DALAM PENGELOLAAN HUTAN DI DESA BAMBASIANG KECAMATAN PALASA KABUPATEN PARIGI MOUTONG - Rosita, Rosita; Rachman, Imran; Alam, Andi Sahri (Universitas Tadulako, 2017)
Society wisdom or local wisdom is human positive behavior in interacting with nature and environment that derives from religion, customs, ancestor advice or local culture value. It occurs naturally in a community to adapt with environment. This behavior developed to a culture in a region and passed on from generation to generation. In general, local culture is defined as culture that developed in a region and the elements are culture of tribes that live in that region. Lauje tribe that live in Bambasiang Village is a community with a great culture identity which covered language and religion system that little different with tribes that live in other district. Objective of the research is to find out local wisdom of Lauje tribe in forest management. Method of the research is descriptive with using snowball sampling method. Based on the research result, the local wisdom of lauje tribe in forest management is still implementing their ancestor faith that already hereditary carried out. Although they manage the forest, they still keep the balance of nature for sake of their survival in the future.Key words: society, forest, Bambasiang Village